2018
DOI: 10.1002/jls.21552
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leader Humility on the Performance of Virtual Groups

Abstract: Personal humility contributes to leadership effectiveness in a number of situations. However, causal mechanisms linking leader humility to positive outcomes appear to vary by task and by context. The present study investigated a mediation model where leader humility was hypothesized to lead to both a sense of psychological safety in the group and an increased sense of liking for the leader when conducting a highly interdependent task in a virtual environment. In turn, psychological safety and liking for the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Experiments are fundamental because they allow scholars to make casual claims (Antonakis et al, 2010; Lonati et al, 2018). Several different experimental designs were employed, including vignettes (e.g., Cojuharenco & Karelaia, 2020; Rego et al, 2019; Swain, 2018; Zhu et al, 2019) and experiential recall (e.g., Qin et al, 2020). These experimental studies highlight the ability to manipulate humble leadership.…”
Section: Methodological Strengths and Weakness Of Humble Leadership R...mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments are fundamental because they allow scholars to make casual claims (Antonakis et al, 2010; Lonati et al, 2018). Several different experimental designs were employed, including vignettes (e.g., Cojuharenco & Karelaia, 2020; Rego et al, 2019; Swain, 2018; Zhu et al, 2019) and experiential recall (e.g., Qin et al, 2020). These experimental studies highlight the ability to manipulate humble leadership.…”
Section: Methodological Strengths and Weakness Of Humble Leadership R...mentioning
confidence: 99%
“…In addition to impacting followers, humble leadership can similarly benefit teams and increase information flow (Swain, 2018). Finally, humble leadership also influences a leader's own subsequent behavior.…”
Section: Humble Leadership Theories and Nomological Netmentioning
confidence: 99%
“…In line with the same reasoning, we argue that employees working under leaders who are high in humility may perceive a sense of relief from high involvement at the cost of family time. It may happen because they may feel heard of their concerns, care about their family life and observe empathetic leaders understand their issues (LaBouff et al, 2012;Swain, 2018). Employees' perception of such social support and altruistic behavior, characterized in humble leadership, is less likely to perceive an imbalance in their work and family life.…”
Section: The Moderation Of Humble Leadershipmentioning
confidence: 99%
“…However, knowledge sharing in a team does not happen spontaneously, and leadership style affects the knowledge sharing and knowledge integration behaviors of members of an organization [48,49].The process of technology standard innovation requires engaging members from different organizations to participate in the activity to facilitate an information flow through collecting, processing, analyzing, and integrating knowledge. Swain [50] has shown that the humility of a leader can smooth the information flow in a team. This implies that humble leadership may have a positive impact on the exchange and combination of knowledge in the team, so we propose: Hypothesis 1.…”
Section: Humble Leadership and Knowledge Exchange And Combinationmentioning
confidence: 99%